Organizational Transfer and Class Structure - Farmer, Richard N. (Academy of Management Journal, 1966)
Nations borrowing technology from more developed countries often fail to realize that much of the developed country's class structure, behavior and attitude are often implicitly built into its technology. Thus, a developing nation may be obtaining more than it bargained for in such technological borrowing. The developing country may either have to change its own class structure or partially fail in its efforts to borrow. This paper examines some of the reasons why class structures are built into technology and what some of the implications of such technological borrowing are.